Pengaruh Model Pembelajaran Guided Inquiry dengan Integrasi SSI terhadap Keterampilan Berpikir Kreatif dan Literasi Biologi Siswa SMA di Sekolah Agroekosistem - Sri Setyawati Utami (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Biology learning activities at SMAN Pakusari still rely heavily on memorizating and rote recall, which is considered inadequate in developing 21st-century skill. This study aims to: 1) analyze the effect of the guided inquiry learning model integrated with Socio-Scientific Issues (SSI) on the creative thinking skills of high school students in agroecosystem area schools; and 2) analyze the effect of the guided inquiry learning learning model integrated with Socio-Scientific Issues (SSI) on the biological literacy skills of high school students in agroecosystem area schools. This study employed a quasi-experimental method. The research population consisted of all grade X students at SMAN Pakusari, Jalan PB. Sudirman 120, Pakusari, Pakusari District, Jember Regency, East Java Province, compiring 7 classes. Sample were selected using random sampling, resulting in class X3 as the experimental class, which was taught using the guided inquiry learning model integrated with Socio-Scientific Issues (SSI), while the class X5 as the control class, used a conventional learning model with a question and answer method. Research result were analyzed using ANACOVA. The findings indicate that: 1) a significance value of 0.023 (sig <0.05) was obtained, meaning thre is a effect of the guided inquiry learning model integrated with Socio-Scientific Issues (SSI) on the creative thinking skills of high school students in agroecosystem area schools; and 2) a significance value of 0.019 (sig <0.05) was obtained, meaning there is a effect of the guided guided inquiry learning model integrated with Socio- Scientific Issues (SSI) on the biological literacy skills of high school students in agroecosystem area schools. It can be concluded that guided inquiry learning model integrated with Socio Scientific Issues (SSI) is effective in improving both creative thinking and biological literacy skills among high school students in agroecosystem-based school environments.
-
Reva_21 Mei 2026
Keywords: biological literacy; creative thinking; guided inquiry.